2014
DOI: 10.1111/risa.12297
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Risks of Cancer from Drywall Finishing Based on Stochastic Modeling of Cumulative Exposures to Respirable Dusts and Chrysotile Asbestos Fibers

Abstract: Sanding joint compounds is a dusty activity and exposures are not well characterized. Until the mid 1970s, asbestos-containing joint compounds were used by some people such that sanding could emit dust and asbestos fibers. We estimated the distribution of 8-h TWA concentrations and cumulative exposures to respirable dusts and chrysotile asbestos fibers for four worker groups: (1) drywall specialists, (2) generalists, (3) tradespersons who are bystanders to drywall finishing, and (4) do-it-yourselfers (DIYers).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The authors noted that their estimate was "an order of magnitude lower" than the value of 12-26 f/cc-year presented earlier in Phelka and Finley (2012). They attributed this difference to Verma and Middleton's assumption that a drywaller would spend 25-30% of their week performing sanding tasks, which was far greater than the value of 1-11% determined by Boelter et al (2015). It is unclear why their observations differed.…”
Section: Predictive Modelsmentioning
confidence: 71%
See 3 more Smart Citations
“…The authors noted that their estimate was "an order of magnitude lower" than the value of 12-26 f/cc-year presented earlier in Phelka and Finley (2012). They attributed this difference to Verma and Middleton's assumption that a drywaller would spend 25-30% of their week performing sanding tasks, which was far greater than the value of 1-11% determined by Boelter et al (2015). It is unclear why their observations differed.…”
Section: Predictive Modelsmentioning
confidence: 71%
“…The authors concluded that the fiber concentrations estimated with the new model were not significantly different from fiber concentrations measured during the historical use of asbestos-containing joint compound, for both enclosed and non-enclosed environments (Brorby et al 2012). Boelter et al (2015) calculated cumulative asbestos exposures for the sanding tasks performed by drywallers based on previously published survey data, direct field observations from contemporary construction worksites, and a semi-empirical mathematical model (Boelter et al 2015). At each worksite, the investigator recorded the dimensions of the floor and wall area, and task-specific durations (drywall installation, tape and joint compound application, sanding, and other activities), and calculated the sanding speed for the drywaller.…”
Section: Predictive Modelsmentioning
confidence: 88%
See 2 more Smart Citations
“…The predicted eight‐hour TWA airborne asbestos fibers concentrations are not above current or historical occupational exposure limits (OELs). Estimated exposures (dose) to airborne asbestos fibers are not in the range associated with elevated rates of lung cancer or mesothelioma . Although relative exposure risks are very low regarding the handling of ceiling panels, continued diligence in the use of built environment bulk material survey techniques as well as management and abatement methods are appropriate precautions as conditions above the ceiling may be unknown.…”
Section: Resultsmentioning
confidence: 99%